Decision-Making on Working Capital Management, Based on Industry Differences - Tsangari, Haritini (International Journal of Business, Economics and Management, 2019)
The effect of working capital components on profitability has conflicting empirical evidence, which is mostly data-driven. This paper aims to provide additional insight to this end, especially focusing on the neglected aspect of industry differentiation. The analysis implements a panel regression methodology on a dataset of 300 observations from firms in Cyprus, adjusting for control variables and considering industry differences. Overall, the present study illustrates that industry differences warrant in-depth examination for decision-making regarding working capital management policies. The findings show that the cash conversion cycle and its components have an effect on profitability, but the sign and level of significance vary according to the industry sector: results in the merged sample differ from the results by industry sector. For example, the cash conversion cycle has a positive effect on the consumer goods sector and a negative effect in the industrials sector. Additionally, management of creditors and suppliers is as important as the management of debtors, especially for consumer goods and industrials. Managers should aim for the optimal level of the working capital components, while simultaneously adjusting their strategies based on their industry sector, to boost firm profitability.